«Музей» С. М. Даниэля: Текст и структура аудитории [“Muzei” by Sergei Daniel: The Text and the Structure of its Audience] - Danilevsky, Alexander (Slavica Revalensia, 2017)
This article applies the method of Yuri Lotman’s article “The Text and the Structure of Its Audience” to the study of Sergei Daniel’s autobiographical novel Muzei (2012). It shows that the ideal reader of Muzei should be competent in a) the topography of Leningrad (St. Petersburg), b) Russian history, c) Greek mythology, d) history of philosophy, e) technicalities of the profession of a painter, f) history of arts, g) theories of art, h) history of Russian literature, and many other fields.